Competition in treasury auctions - Helmut Elsinger; Philipp Schmidt-Dengler; Christine Zulehner (Austrian Institute of Economic Research (WIFO), 2016)
We investigate the role of competition on the outcome of Austrian Treasury auctions. Austria's EU accession led to an increase in the number of banks participating in treasury auctions. We use structural estimates of bidders' private values to examine the effect of increased competition on auction performance: We find that increased competition reduced bidder surplus substantially, but less than reduced form estimates would suggest. A significant component of the surplus reduction is due to more aggressive bidding. Counterfactuals establish that as competition increases, concerns regarding auction format play a smaller role.
Keywords: D44; G12; G21; L10; L13; 330; treasury auctions; multi-unit auctions; independent private values; competition; bidder surplus; auction format